The effectiveness of English teaching program in senior high school: A case study - Irambona, Alfred; Kumaidi, Kumaidi (REID (Research and Evaluation in Education), 2015)
This research seeks to evaluate the effectiveness of the English teaching program in senior high school: Case of SMAN3 Yogyakarta, grade eleven. This study was a summative case study using a mixed-method. Descriptive statistics were used to analyze quantitative data and qualitative data followed a descriptive analysis following the CIPP model. The informants were 43 students of SMAN3 and two English teachers. The context findings showed that program objectives, classroom condition, students’ needs and barriers were in effective category. In input component, it is found that both teachers were qualified and experienced. The teaching training was not enough; students’ textbooks and course designs were in effective category. The process component showed that teaching materials, teaching methods, teaching activities and assessments were in effective category. The product component showed that English marks, students’ needs and barriers were in effective category. However, the teaching materials were in "˜not effective’ category.